The dual effects of riboflavin and kelp polyphenol extracts on the gel properties of myofibrillar protein from Scomberomorus Niphonius under UVA irradiation. (1st December 2020) - He, Baoyu; Ming, Yu; Pu, Yuan; Sun, Yihan; Jin, Meiran; Yu, Chenxu; Qi, Hang
Highlights: Hydroxyl radicals were produced by RF under UVA irradiation. A part of KPE plays anti-oxidation under UVA irradiation to avoid MP peroxidation. The presence of both RF and KPE moderate oxidize MP and improve gel performance. Abstract: In the present study, effects of riboflavin (RF) and kelp polyphenol extracts (KPE) on mackerel ( Scomberomorus Niphonius ) myofibrillar protein (MP) gel were studied with or without ultraviolet A (UVA) irradiation treatment. The gel strength was increased with the addition of RF and KPE under UVA irradiation. Analysis of the proteins in the gel indicated that the carbonyl content increased, while the contents of total sulfhydryl and amino groups decreased. The proteins appeared to have no α-helix structures, and the endogenous tryptophan content appeared to decrease. The results of SDS-PAGE indicated that the RF and KPE treated samples under UVA irradiation showed massive MP cross-linking by covalent bonds. Electron spin resonance (ESR) results indicated that UVA irradiation generated free radicals in RF and KPE, which ultimately led to an improvement in MP gel properties. It also indicated that KPE could prevent the occurrence of peroxidation to improve the gel properties.